Predictive performance of serum adipsin combined with 25(OH)D for peripheral neuropathy in elderly diabetic patients - Wu, Yi; Li, Menglu; Cui, Yu; Su, Dan; Qian, Xiaodan; Tang, Lidan; Yang, Hao; Xu, Shan (Journal of Medical Biochemistry, 2025)
Objective: Diabetic peripheral neuropathy (DPN) is a common chronic complication in older adults with type 2 diabetes mellitus (T2DM). Early diagnosis is essential for delaying disease progression. This study set out to explore the predictive value of the combined detection of serum adipocytokine adipsin and 25-hydroxyvitamin D [25(OH)D] in elderly DPN patients, and to provide new strategies for early intervention. Methods: Based on the electronic medical records of our hospital from January 2024 to June 2025, 150 elderly patients with T2DM (104 in DPN group and 57 in non-DPN group) were enrolled. Serum adipsin was detected by ELISA, and 25(OH)D was measured via chemiluminescent immunoassay. The diagnostic efficacy of the combined detection was confirmed by univariate analysis, Logistic regression model, and ROC curves. Disease course and age-stratified subgroup analyses were further carried out. Results: DPN patients showed higher serum adipsin but lower 25(OH)D levels than non-DPN cases (P<0.05). Adipsin + 25(OH)D detection exhibited an AUC of 0.831 (sensitivity: 64.42%, specificity: 87.72%), higher than single-index predictions. Subgroup analysis indicated superior prediction efficiency of the combined detection in patients with a course of disease ≥6 years (AUC>0.85). According to correlation analysis, adipsin was positively correlated with FPG, HbA1c, and VPT, and negatively correlated with NCV and SCV; while the opposite was true for 25(OH)D. Conclusion: Serum adipsin combined with 25(OH)D has high predictive value for elderly DPN, and their synergistic effect may be exerted through the "inflammation-oxidative stress-metabolic disorder" axis.